Body sway and aim point fluctuation in rifle and pistol shooters - Ball, K. (1999)
This study examined the effects of quantisation of force plate data used to measure body sway and the relationship between this body sway, aim point fluctuation and performance in shooting. Quantisation error in and resolution of selected body sway parameters were calculated from force plate data sampled using 12-bit and 16-bit analog to digital conversion (ADC). It was concluded that 12-bit ADC does not offer adequate precision when assessing the body sway of shooters and that 16-bit ADC is required. The relationship between body sway, aim point fluctuation and performance was examined on both group and individual bases. Body sway was measured in six elite rifle and five elite pistol shooters while performing 20 shots in simulated competition conditions over 5s, 3s and 1s before shot using an AMTI LG6-4 force plate and 16-bit ADC. This was synchronised with a SCATT shooting training analysis system, which measured aim point fluctuation and performance. From 16 time-based body sway parameters quantified, principal components analysis identified four body sway factors, which related to the amplitude and speed of this sway in both the X and Y axis. Using four body sway parameters that represented these factors, correlation and multiple regression analysis indicated that body sway, aim point fluctuation and performance were related for some but not all shooters. Further, this association was specific to the individual shooter in terms of degree and direction of association, the axis of influence of body sway and aim point fluctuation and the time period. This highlighted the importance of individual based analysis in elite shooting. Further research with larger subject numbers, aim point fluctuation more thoroughly examined and including kinematic analysis may assist in better defining the relationship between body sway, aim point fluctuation and performance.